Management of Malayan sun bear (Helarctos malayanus) in Bornean Sun Bear Conservation Centre, Sepilok Sandakan Sabah with emphasis on deworming program - Aziz, Fatin Nabilah (2015)
Endoparasites play an important role in the health status of captive wild animals. This study aims to determine the effectiveness of deworming program related to the management practices done on Malayan sun bear. A cross sectional study was done on 18 of the Malayan sun bear in semi-captive and captive management in the Bornean Sun Bear Conservation Centre in Sepilok, Sandakan Sabah. The sun bears were given anthelmintic Drontal® plus (praziquantel/pyrantel pamoate/febantel) three months before study. Fresh fecal samples were collected from the floor of each bear cages. Standard parasitological techniques which are direct fecal smear, simple floatation, simple sedimentation method and another effective method which is formal ether sedimentation were used to detect the presence of ova in the faces. Results showed no helminth ova were present. The management factors which encompasses routine cleaning, disinfectant used, stocking density and food hygiene appeared effective to prevent endoparasitism in these bears. This study provides evidence that once every three month of Drontal® plus in deworming program adopted in this centre has successfully control helminth infestation. This study is belief to be the first documentation of the effectiveness of the deworming program in a Malayan sun bear conservation center.